Modernization of the circulating water hydrothermal parameters control system at the point of entry into block pump station at NPP - Kosach, N. I.; Beiner, P. S. (Visnyk of Vinnytsia Politechnical Institute, 2015)
The improvements to circulating water hydrothermal parameters control system directly at the point of entry to the block pumping station at NPP are suggested. The calculation of economic benefits from the implementation of the developed system for automated control of circulating water temperature mode at nuclear power plant is carried out in the paper.